2011
DOI: 10.1007/s00726-011-0938-7
|View full text |Cite
|
Sign up to set email alerts
|

Peptides derived from Mycobacterium tuberculosis Rv2301 protein are involved in invasion to human epithelial cells and macrophages

Abstract: The specific function of putative cut2 protein (or CFP25), encoded by the Rv2301 gene from Mycobacterium tuberculosis H37Rv, has not been identified yet. The aim of this study was to assess some of CFP25 characteristics and its possible biological role in Mycobacterium tuberculosis H37Rv invasion process to target cells. Molecular assays indicated that the gene encoding Rv2301 is present and transcribed in M. tuberculosis complex strains. The presence of Rv2301 protein over the bacilli surface was confirmed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Many macrophage receptors are involved in phagocytosis of mycobacteria, such as complement receptor, mannose receptor, and CD14. 1,2 To promote their survival under the pressure of host response, M. tuberculosis bacteria counteract certain cell biological and immune processes involved in the host response, including antigen presentation, pro-inflammatory cytokine secretion and phagosome maturation, so it can survive inside host cells. 3 In the M. tuberculosis genome, two distinctive protein families have been known as the proline−glutamic acid (PE) and the proline−proline−glutamic acid (PPE) families, which represent about the 10% of the coding genes of the genome.…”
mentioning
confidence: 99%
“…Many macrophage receptors are involved in phagocytosis of mycobacteria, such as complement receptor, mannose receptor, and CD14. 1,2 To promote their survival under the pressure of host response, M. tuberculosis bacteria counteract certain cell biological and immune processes involved in the host response, including antigen presentation, pro-inflammatory cytokine secretion and phagosome maturation, so it can survive inside host cells. 3 In the M. tuberculosis genome, two distinctive protein families have been known as the proline−glutamic acid (PE) and the proline−proline−glutamic acid (PPE) families, which represent about the 10% of the coding genes of the genome.…”
mentioning
confidence: 99%
“…This report emphasize the importance of HBHA in M. tuberculosis dissemination, since it has demonstrated that HBHA induces membrane protrusions formation, is possible to infer that HBHA may be one of the mycobacterial molecules that can act as "signals for internalization" hence inducing mycobacteria entrance by macropinocytosis, as previously we suggested (Garcia-Perez et al, 2008). Other molecules of M. tuberculosis responsible of the invasion of epithelial cells are the mycobacterial DNA-binding protein 1 (MDP1), which promotes A549 cells infection through hyaluronic acid (Aoki et al, 2004); and a group of high active bound peptides (HABPs) of different hypothetical proteins from M. tuberculosis (Rv2301, Rv0180c, Rv0679c, among others), which have shown that facilitates the bound and internalization of latex particles to A549 cells (Cáceres et al, 2011;Cifuentes et al, 2010;Ocampo et al, 2011).…”
Section: Epithelial Cells Infection By M Tuberculosismentioning
confidence: 99%
“…Peptides were cleaved by the low-high hydrogen fluoride technique [58], purified by reversed-phase high-performance liquid chromatography and analyzed matrix assisted laser desorption/ionization time-of-flight mass spectrometry. A tyrosine residue was added to the carboxyl-terminus of those peptides not containing this residue in their sequence to enable radiolabeling with Na 125 I [5,40,42,45,50]. Briefly, peptides were individually radio-labeled using 5 L Na125I (100 mCi/mL; MP Biomedicals) and 15 L chloramine-T (2.8 mg/mL) as oxidizing agent.…”
Section: Peptide Synthesismentioning
confidence: 99%
“…Mce family proteins) [16]. Experimental results obtained in our laboratory have led to some Mtb proteins' involvement in such invasion having been described, assessed and characterized in terms of their specific binding ability and role in mycobacterial entry to A549 cells and U937 monocyte-derived macrophages [5,18,40,42,50,59]. Identifying surface proteins (or their specific segments) in intracellular pathogens such as Plasmodium falciparum has been shown to counteract invasion, thereby becoming an important approach in the search for minimal subunit-based, multi-epitope, synthetic vaccine candidates [43].…”
Section: Introductionmentioning
confidence: 99%